Daya Tarik Dan Makna Elegan Bagi Pecinta Fashion Persepsi Anggota Komunitas Hijabi Tentang Foto Fashion Di Majalah - Muhamad Afdoli Ramadoni; Vina Zahratul Hayat (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2023)
This research is motivated by the existence of photography which cannot be separated, especially in the world of fashion. Because fashion, make-up and photography are one unit that always go hand in hand and both need each other. Fashion Photography, Photos that focus on depicting and presenting various clothing and other fashion items related to lifestyle. Creating fashion photos requires experts in their fields, such as professional photographers and models, but also other fashion lovers, be they buyers, fashion experts, bloggers and fashion vloggers. As a community that the author wants to study, namely the Yogyakarta Hijabie community which gave birth to a generation of Muslimah model labels and raised fashion lovers who are good at creating without forgetting to convey their da'wah through fashion da'wah, we preach. syariah This research is a qualitative descriptive research. The results of the observational analysis research to focus on attractiveness and elegance in fashion photos are the perceptions of members of the hijabi community, namely first, the mindset is relatively the same, namely according to individual perceptions of attractiveness and elegance in fashion photos in magazines. Second, connecting the concept of chic objects as a whole which makes it elegant. Third, elegant or glamorous as a form of feeling more confident.